Sosialisasi Pengembangan Teknologi Tepat Guna Mesin Es Balok untuk Mendukung Kemandirian dan Ketahanan Ekonomi Nelayan - Fadli Afriandi; Andika Rahmad Rangkuti; Ligar Abdillah; Cut Nabilla Kesha; Fachriza Ariyadi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2026)
This service program is in the form of socialization activities carried out in Kampung Gosong Telaga Selatan, Aceh Singkil, to overcome the limited supply of ice blocks as a preservative for the catch of traditional fishermen of KUB Nelayan Maju Bersama. This socialization aims to increase the understanding and readiness of fishermen in utilizing appropriate technology in the form of ice block machines. The lecture and discussion method was used in the socialization process, involving 22 participants under the coordination of the Chairman of KUB Nelayan Maju Bersama. The results of this service showed a significant increase in understanding, marked by an increase in post-test scores of 65% compared to pre-tests. This socialization helps fishermen understand the benefits of ice block machines in maintaining the freshness of fish after going to sea, reducing losses, and increasing selling value. This activity also strengthens collective management in the group. Overall, the socialization succeeded in increasing the capacity of fishermen to adopt technology and support local economic independence, while encouraging the sustainability of small-scale fisheries businesses based on participatory and sustainable empowerment of coastal communities, to strengthen the economic resilience of fishing families in the region.